The constructive nonlinearity of a self-stressing steel-reinforced concrete overlapping during uneven deformations of adjacent columns basis - Hasenko, Anton (Academic journal Industrial Machine Building Civil Engineering, 2022)
Constructive nonlinearity during building structures’ calculation takes into account the change in the free body diagram of their operation. One of the cases of structurally nonlinear work of steel-reinforced concrete overlapping structures is possible uneven deformation of building transverse frame adjacent columns basis. In the course of setting research objectives, was formulated eight conditions of structurally nonlinear operation of steel-reinforced-concrete overlapping beams, distinguished by uneven subsidence of the building’s transverse frame outermost or middle columns and rigid or hinged junctions connecting the overlapping beams to the columns. Also, for each of the mentioned combinations of column subsidence and types of beam-to-column connection nodes, the effect of installing braces under the main overlapping beams, deformed by their weight, was investigated. The calculation of two or more nonlinear systems with specified boundary conditions is performed using numerical methods of finite element modelling, implemented in the Software Package Femap 2020.2 with NX Nastran.